Morality, Internal Control, and Regulatory Compliance: Foundations for Preventing Fraud in Village Funds - Mokoginta, Rena Mustari; Jeandry, Gregorius (Cita konsultindo, 2024)
This study aims to analyze the influence of morality, internal control, and compliance with accounting rules on fraud prevention in village fund management. The research employs a quantitative method with a saturation sampling technique, where the entire population of village officials involved in financial management in the North Tidore District—including village heads, village secretaries, village treasurers, and the heads of the Village Consultative Body (BPD)—was used as the sample. The total sample for this study is 88 individuals. Data collection was carried out through a questionnaire that had been tested for validity and reliability. The results indicate that all three variables—morality, internal control, and compliance with accounting rules—significantly influence fraud prevention. Morality plays an essential role in shaping individual integrity, reducing the propensity to commit fraud. Effective internal control also proves to be capable of preventing fraud by establishing a rigorous oversight system. Compliance with accounting rules helps maintain transparency and accountability in financial reporting, ultimately reducing the opportunities for financial manipulation. However, the effectiveness of these three variables is greatly influenced by organizational context and external supervision. In conclusion, morality, internal control, and compliance with accounting rules are key foundations in fraud prevention in village fund management, which must be integrated with sound governance policies and consistent law enforcement.